048 Post-mortem translocation analysis using 16S sequencing. (December 2018) - Gates, L; Sebire, N; Klein, N; Alber, D
Abstract : Background: The diagnostic potential of post-mortem bacteriology has been a topic of debate since its introduction to clinical pathology due to false-positive results. A possible source of false-positive results is post-mortem translocation which is the migration of microbial species from sites such as the gastrointestinal (GI) tract to the blood or other tissues. This phenomenon makes it difficult for pathologists to identify cases of true ante-mortem infection leading to possible misdiagnosis. Methods: A mouse model was used to assess the microbiome in the blood, heart, lung, spleen, liver and GI tract over a 14 day period. Fifteen surplus mice were acclimatised in three separate cages for seven days prior to sacrifice. One mouse from each cage was sampled at each time point (0, 3, 7, 10 and 14 days post-death). The microbiome was characterised through next-generation sequencing of the v3/v4 region of the bacterial 16S rRNA gene. Results: All 45 GI samples could be amplified by 16S rRNA gene sequencing compared to only 12/75 of remaining tissue samples. Following sequencing, 13/57 samples were removed from analysis due to low sequencing reads, with all remaining samples from the GI tract. There was an increase in alpha and beta diversity from day 0 to day 10 with a decrease in diversity at day 14. In terms of phyla abundance, as time post-death increased there was an increase in the abundance of Actinobacteria, Deferribacteraceae and Tenericutes. Conclusion: Although this study found changes in the gut microbiome, the inability to sequence bacteria in other tissues suggests little translocation occurred over the time period. To assess whether this is model-specific, this study is to be repeated in a model more closely related to humans. With the development of molecular techniques and interest in this method for post-mortem diagnostics, it is imperative to understand the significance of bacterial translocation.